Case Report: Difficulties in the Treatment of a 12-Year-Old Patient With Homozygous Familial Hypercholesterolemia, Compound Heterozygous Form − 5 Years Follow-Up - Vladimirova-Kitova, Lyudmila; Kitov, Spas; Ganev, Mihail; Chochkova-Bukova, Lubov (Frontiers in Cardiovascular Medicine, 2021)
The literature review we conducted reveals a limited use of proprotein convertase subtilisin/kexin type 9-inhibitors (PCSK9i) in children with Familial hypercholesterolemia (FH). In 2015, a 10-year-old boy presented with round, xanthochromic lesions on his right knee and elbow. The values of total and LDL-cholesterol (LDL-C) - 18 mmol/l and 15 mmol/l, respectively, along with normal triglycerides and HDL-cholesterol (HDL-C) confirmed the lesions were xanthomas. The data suggested a homozygous form of FH. The level of Lipoprotein (a) was high - 270 mg/dl. Initial treatment, based on European recommendations, included Atorvastatin 20 mg and Ezetimibe 10 mg, and led to a decrease in LDL-C by 46% for 5 months, however, the patient developed severe statin intolerance. Atorvastatin was replaced with Rosuvastatin 10 mg, but the symptoms persisted. Success was achieved by switching to an intermittent regimen - Rosuvastatin 10 mg three times a week with a daily intake of Ezetimibe 10 mg. However, the results were far from the desired LDL-target. LDL-apheresis was advisable but, unfortunately, it is not performed in Bulgaria. In May 2017 a genetic analysis (two pathological mutations within the LDLR gene: c.1519A>G; p.(Lys507Glu) and c.2403_2406del; p.(Leu802Alafs*126)) confirmed the initial diagnosis – the patient had homozygous FH with compound heterozygosity, indeed. Having turned 12, in September 2017, the patient was eligible for treatment with a PCSK9i - Evolocumab 140 mg. The mean reduction of LDL-C with the triple combination reached a reduction by 52.17% for the whole 2-year period. The LDL target was reached in January 2020. The triple therapy significantly reduced Apolipoprotein B by 29.16%. No statistically significant difference was found in Lp (a) levels. (p˃0.05) Our clinical case demonstrates that the triple lipid-lowering combination in a patient with compound heterozygous FH is a good therapeutic option for reaching the LDL-target.